A Comparative Analysis of Choorna and Bhavitha Choorna of Dried Rhizome of Haridra (Curcuma Longa Linn.) Through High Performance Thin Layer Chromatography - Saswathy , T R; Shincymol , V V; Ansary, P Y; Oommen, Sara Monsy (International Research Journal of Ayurveda & Yoga, 2022)
The drug Haridra (Curcuma longa Linn.) has been extensively used as medicine and strongly relates to the socio-cultural life of people. The rhizome of the plant is rich in phytoconstituents which are responsible for the pharmacological actions of the drug. HPTLC serve as a potent tool for identification, authentication and quality control of herbal medicines in order to get the genuine drug. The present study aimed to compare the choorna (powder) and bhavitha choorna (processed powder) of the methanol extract of the dried rhizome of Haridra (Curcuma longa Linn.) through high-performance thin layer chromatography. HPTLC plates Silica gel 60 F 254, 4.0 x 9.0 cm aluminum sheet was the stationary phase. Mobile phase comprising Toluene: Ethyl acetate: formic acid (6:3:0.1). The development of the plate was done by using CAMAG 20 x 20 cm automatic developing chamber. After derivatization using anisaldehyde sulphuric acid reagent, it was visualized under UV at 254 nm and 366 nm. The number of peaks in the chromatogram of bhavitha choorna (processed powder) was more when compared to choorna (powder) at 254nm indicating a greater number of phytoconstituents in bhavitha choorna (processed powder). The total area of bhavitha choorna (processed powder). is more than choorna(powder) of the drug at 366nm indicates that the concentration of phytoconstituents has been increased by the process of bhavana which substantiate that bhavana process can increase the potency and efficacy of the drug.